Optimization of the controller`s parameters of the gas-diesel generator unit - Ryabenkiy, V. M.; Ushkarenko, A. O. (Видавництво Львівської політехніки, 2012)
This article gives the rationale of the possibility of using PID control systems in the gas-diesel engines.
Keywords: electric power; power distribution; as diesel engine